Human Capital Prices, Productivity, and Growth - Bowlus, Audra J; Robinson, Chris (American Economic Review, 2012)
Separate identification of the price and quantity of human capital has important implications for understanding key issues in economics. Price and quantity series are derived for four education levels. The price series are highly correlated and they exhibit a strong secular trend. Three resulting implications are explored: the rising college premium is found to be driven more by relative quantity than relative price changes, life-cycle wage profiles are readily interpretable as reflecting optimal human capital investment paths using the estimated price series, and adjusting the labor input for quality increases dramatically reduces the contribution of MFP to growth. (JEL D91, I20, J24, J31, O47)